14.2: Reduction of speckle noise by spatial‐multiplexing pixel separation in computer generated holographic display. (4th October 2019) - Jia, Jia; Tan, Baolin; Kang, Jianghui; Pu, Yiying; Wu, Yu
Abstract : To reduce the speckle noise in a holographic display, a method by separating the pixel or object points of reconstructed images is proposed using a light source array. The multiple sparse images are reconstructed and shifted together to form the complete images with the speckleless noise. The simulation results show that the speckle noise is reduced from 51% to 21% by using a 3 × 3 light source array. It is expected that it could be used for realizing a dynamical 3D holographic display with the less speckle noise in the future.